Spirituality: sense and gist. On meaning, God and being - C. Lombaard (Acta Theologica)
The definition of spirituality is a notoriously difficult undertaking. Rather than continuingly pointing this out, two advances are suggested in this article: That the impossibility of a precise definition of spirituality is accepted, as is the case with many other important aspects of life, and that the inherently paradoxical nature of spirituality is more fully explored as a way of coming to a deeper understanding of this phenomenon. The latter is illustrated by briefly juxtaposing the concepts of God and non-God and of self-implication and estrangement. The most important books for furthering such analyses are listed.